2020
DOI: 10.3389/fcimb.2020.588195
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Cannabinoid Receptor Type 2 Agonist Modulates the Polarization of Microglia Towards a Non-Inflammatory Phenotype in Experimental Pneumococcal Meningitis

Abstract: Background: Microglia initiates and sustains the inflammatory reaction that drives the pathogenesis of pneumococcal meningitis. The expression of the G-protein cannabinoid receptor type 2 (CB2) in the brain is low, but is upregulated in glial cells during infection. Its activation down-regulates pro-inflammatory processes, driving microglia towards an antiinflammatory phenotype. CB2 agonists are therefore therapeutic candidates in inflammatory conditions like pneumococcal meningitis. We evaluated the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, Pan et al observed a shift of microglia towards an anti-inflammatory phenotype in the hippocampus and cortex by administering the agonist JWH-133 in a pneumococcal meningitis paradigm [ 111 ]. In animal models of alcoholism, the administration of the CB 2 r agonist AM1241 promoted liver regeneration in a thioacetamide (TAA)-induced liver injury model by suppressing TLR4/miR-155/NF-κB p65 pathway [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Pan et al observed a shift of microglia towards an anti-inflammatory phenotype in the hippocampus and cortex by administering the agonist JWH-133 in a pneumococcal meningitis paradigm [ 111 ]. In animal models of alcoholism, the administration of the CB 2 r agonist AM1241 promoted liver regeneration in a thioacetamide (TAA)-induced liver injury model by suppressing TLR4/miR-155/NF-κB p65 pathway [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specific deletion of Cannabinoid Receptor 2 (CB2) receptors in microglia and dopamine neurons has been shown to induce neuroinflammation, alter locomotor activity, and induce behavioral changes via alcohol [60]. JWH-133 (dimethylbutyl-deoxy-delta-8-THC), a selective agonist of CB2, has been shown to reduce the cytokine levels, such as CINC-1, -2α/β, and MIP-3α, in parenchymal cells and change microglia towards the non-inflammatory phenotype; however, it could not reverse or ameliorate brain damage [61]. Microglia express several receptors depending on the proinflammatory or anti-inflammatory environment prevailing within the vicinity.…”
Section: Expressions and Activation Of Receptors In Microgliamentioning
confidence: 99%
“…Staining and categorical analysis of microglia morphology. Brains collected at 42 hpi were sampled into 45 µm free-floating cryosections and stained with Iba-1 for microglia as previously described 58 . Images of microglia in the cortex were randomly sampled under × 400 magnification from each animal (three sections per animal).…”
Section: Histomorphometric Analysis Of Cortical Damage and Hippocampa...mentioning
confidence: 99%
“…Images of microglia in the cortex were randomly sampled under × 400 magnification from each animal (three sections per animal). Cells were classified into three categories, as previously described 58 : resting = round, oval body with thin and long processes; intermediate/hypertrophied = enlarged, darkened cell body with thick processes and less branching; reactive = enlarged, darkened cell body with little or no processes. The percentage of the different categories was calculated by first counting the total microglial cell number in the image followed by counting the three states of the microglia.…”
Section: Histomorphometric Analysis Of Cortical Damage and Hippocampa...mentioning
confidence: 99%